Retrieval-induced versus restudy-induced forgetting in serial order memory. - Kobayashi, Masanori; Ueno, Taiji; Kawaguchi, Jun (Memory & Cognition, 2026)
The nature of forgetting has long been a critical issue in the study of serial order memory, with output interference recognized as a significant factor in shaping serial position curves. However, it remains unclear whether this interference arises from active representations following retrieval (such as capacity consumption, overwriting of other items, blocking retrieval of other information, increased competitions) or if it stems directly from the act of retrieval itself. The present study sought to clarify these possibilities by utilizing retrieval-induced forgetting paradigms, which have been primarily developed within the domain of single-item memory. Through four preregistered experiments, we found that engaging in retrieval practice for part of an ordered list led to reduced order accuracy for the remaining list items. However, the effect size of this retrieval practice was comparable to that of merely re-presenting order information in working memory without engaging in retrieval, suggesting that the observed impairment was not retrieval-specific. This retrieval unspecificity was replicated in an additional experiment. This indicates that output interference in serial order memory is more likely attributable to active representations maintained in working memory, rather than being a direct consequence of retrieval. These findings are discussed within the framework of the two-factor account of retrieval-induced forgetting in the domain of item memory, which posits that both inhibition and competition play roles in the forgetting process.